Analisis Pemantauan Kualitas Tanah untuk Optimalisasi Irigasi pada Pertanian Cerdas - M.Sultan Haidar; Tata Sutabri (Politeknik Kampar, 2024)
The continuous increase in global population presents significant challenges in meeting the world's food needs, particularly in the agricultural sector, which is foundational to food security. This research focuses on the analysis of soil quality monitoring for optimizing irrigation in smart agriculture, utilizing Internet of Things (IoT) technology. The study employs a quantitative descriptive approach to evaluate the relationship between monitored soil quality parameters—such as moisture, pH, and temperature—and water use efficiency in irrigation systems. Real-time data collected from IoT sensors enables farmers to make informed decisions regarding irrigation timing and volume, thereby conserving water resources and enhancing crop yields. The findings indicate a strong correlation between optimal soil moisture levels and increased irrigation efficiency, with potential improvements of up to 75%. This research underscores the necessity of integrating modern technology in agricultural practices to address global food security challenges and promotes sustainable resource management. Future studies should explore the integration of big data and artificial intelligence to further enhance the effectiveness of smart agricultural systems.